SWI/SNF Complex-Deficient Soft Tissue Neoplasms: A Pattern-Based Approach to Diagnosis and Differential Diagnosis - Agaimy, Abbas (Surgical Pathology Clinics, 2019)
Loss of different components of the Switch/sucrose nonfermentable (SWI/SNF) chromatin remodeling complex has been increasingly recognized as a central molecular event driving the initiation and/or dedifferentiation of mostly lethal but histogenetically diverse neoplasms in different body organs. This review summarizes and discusses the morphologic and phenotypic diversity of primary soft tissue neoplasms characterized by SWI/SNF complex deficiency with an emphasis on convergent and divergent cytoarchitectural patterns.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Epithelioid sarcoma; Extraskeletal myxoid chondrosarcoma; INI1; Myoepithelial carcinoma; Rhabdoid tumor; SMARCA4; SMARCB1; SWI/SNF complex; Undifferentiated pediatric sarcoma